Zeetings review: The mash-up of powerpoint and polling (Journal of Applied Learning and Teaching, 2020)
Zeetings is a relatively new tool in the rich world of Educational Technology (EdTech). It combines the standard features of a slide platform, such as PowerPoint, with online polling functionality, such as Kahoot! I began using Zeetings after feeling stifled by the passive nature of my online academic professional development sessions. I wanted to create more engaging lessons that allowed my academics to enjoy deeper learning opportunities. I present two case studies of professional development sessions at Kaplan Business School using Zeetings in two different pedagogical ways – live and flipped. Anecdotally, the academics who participated in the workshops enjoyed using the tool. From a facilitator’s standpoint, Zeetings appeared to provide them with more quality engagement with the content. Embedding formative and summative polling activities throughout the session increased participant engagement and gave me the opportunity to tailor my session according to the responses received. This allowed me to provide just-in-time feedback to my participants which offered them deeper learning opportunities. Zeetings is an easy to use product that achieves its aim of creating enriching and active learning experiences.